2016
DOI: 10.12688/f1000research.8235.1
|View full text |Cite
|
Sign up to set email alerts
|

Post-chikungunya chronic inflammatory rheumatism: results from a retrospective follow-up study of 283 adult and child cases in La Virginia, Risaralda, Colombia

Abstract: Objective: There are limited studies in Latin America regarding the chronic consequences of the Chikungunya virus (CHIK), such as post-CHIK chronic inflammatory rheumatism (pCHIK-CIR). We assessed the largest cohort so far of pCHIK-CIR in Latin America, at the municipality of La Virginia, Risaralda, a new endemic area of CHIK in Colombia. Methods: We conducted a cohort retrospective study in Colombia of 283 patients diagnosed with CHIK that persisted with pCHIK-CIR after a minimum of 6 weeks and up to a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 25 publications
6
27
0
6
Order By: Relevance
“…Geriatric population has been reported to be affected in a more pronounced manner with a prolonged chronic phase as compared to individuals of younger age affected by the infection31. Our sample cohort in the present study also revealed that the median age was the maximum in case of CHIK (Table 1).…”
Section: Resultssupporting
confidence: 66%
“…Geriatric population has been reported to be affected in a more pronounced manner with a prolonged chronic phase as compared to individuals of younger age affected by the infection31. Our sample cohort in the present study also revealed that the median age was the maximum in case of CHIK (Table 1).…”
Section: Resultssupporting
confidence: 66%
“…The worldwide emergence of CHIKV has created a need to identify treatments, as epidemiological estimates suggest there are millions suffering from acute arthritis and at least ~400,000 people in the Western Hemisphere suffering from chronic CHIKV arthritis (5, 8). We reasoned that established therapies used to treat other forms of inflammatory arthritis (for example, rheumatoid or psoriatic arthritis) also might mitigate CHIKV arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…CHIKV and other arthritogenic alphaviruses directly invade the synovium to cause inflammatory arthritis (4), which is characterized by articular swelling and prolonged morning stiffness (3). CHIKV-induced arthritis in humans can persist, with as many as 60% of individuals progressing to chronic disease that lasts from months to years (3, 57). Epidemiological projections suggest that there are currently about 400,000 individuals in the Western Hemisphere with chronic CHIKV arthritis (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, 7%–79% of case-patients from previous outbreaks have reported persistent arthralgia for months after infection ( 4 8 ). Persistent arthralgia associated with CHIKV illness has been assessed in persons in Southeast Asia, South America, and Europe but not in the Caribbean ( 4 , 9 ). …”
mentioning
confidence: 99%